Biased and Biasing: The Hidden Bias Cascade and Bias Snowball Effects - Itiel E. Dror (Behavioral Sciences)
Cognitive bias is widespread, hidden, and difficult to deal with. It impacts each and every aspect of the justice and legal systems, from the initial engagement of police officers attending the crime scene, through the forensic examination, and all the way to the final outcome of the jurors’ verdict and the judges’ sentencing. It impacts not only the subjective elements in the justice and legal systems but also the more objective scientific elements, such as forensic fingerprinting and DNA. The impact of bias on each of these elements has mainly been researched and considered in silo, neglecting the biasing interactions and how bias cascades and snowballs throughout the justice and legal systems. These should happen rarely, as the Swiss cheese model shows that such errors in the final outcome rarely occur because they require that the shortcomings in each element be coordinated and aligned with the other elements. However, in the justice and legal systems, the different elements are not independent; they are coordinated and mutually support and bias each other, creating and enabling hidden bias cascade and bias snowball effects. Hence, minimizing bias requires not only taking measures to reduce bias in each of the elements but also a wider perspective that addresses bias cascade and bias snowball effects.